The incidence of the lack of appropriate methodology to teach English reading in the 10th grade "A" at "San Rafael" School - Cabrera Salazar, Alexandra (2007)
This study describes a reading program conducted at a secondary school in Quito, aimed at motivating the students to read in English and helping them overcome their problems in understanding English texts as a means towards increasing their proficiency in the language. Chapter I, begins by discussing the rationale for problems in the reading for students in high school, the aims and features of the reading, the materials used, as well as the perceptions of students undergoing the problems. The problems faced by the students in understanding texts written in English are particularly highlighted, and implementation of reading in "San Rafael" school. Chapter II, suggests that one of the best ways to help students increase their language proficiency is to encourage them to read. As a result of an examination of research on in-school reading and "out of school" self-reported, concludes that free voluntary reading or sustained independent reading results in better reading comprehension. Chapter III, suggests that the success of a reading depends on several factors, among which are: How teachers are able to motivate the students to read; how the reading is organized and implemented; and how their reading is monitored. Chapter IV, depends on how teachers feel about reading. Unless the teachers are of the view that reading is beneficial in promoting English language development among their students, they are not likely to exert their efforts to make the reading a success.